2021
DOI: 10.2807/1560-7917.es.2021.26.9.1900606
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of whole genome sequencing for pathogen identification and surveillance – results of case studies in Europe and the Americas 2016 to 2019

Abstract: Background Whole genome sequencing (WGS) is increasingly used for pathogen identification and surveillance. Aim We evaluated costs and benefits of routine WGS through case studies at eight reference laboratories in Europe and the Americas which conduct pathogen surveillance for avian influenza (two laboratories), human influenza (one laboratory) and food-borne pathogens (five laboratories). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 11 publications
(5 reference statements)
0
25
0
Order By: Relevance
“…Other countries and different geographic regions have different baseline regulatory climates and food safety cultures, so the marginal effect of WGS source tracking may vary from what we observe in US data [ 30 , 31 ], but this study provides strong evidence for a significant improvement in food safety anywhere WGS source tracking is implemented. WGS surveillance technology is transferable to other international food safety agencies and should be a part of capacity building and partnership programs.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Other countries and different geographic regions have different baseline regulatory climates and food safety cultures, so the marginal effect of WGS source tracking may vary from what we observe in US data [ 30 , 31 ], but this study provides strong evidence for a significant improvement in food safety anywhere WGS source tracking is implemented. WGS surveillance technology is transferable to other international food safety agencies and should be a part of capacity building and partnership programs.…”
Section: Discussionmentioning
confidence: 53%
“…The net benefits presented here, drawn from complete data on only Salmonella outbreaks investigated by FDA from 1999–2019, are more conservative and suggest that the benefits from Salmonella reduction would not approach $90 million dollars until 2019, five years after implementation of the program. Ford et al and Alleweldt et al recently published break-even analyses suggesting that WGS source tracking programs would need to prevent between 0.2% and 2% of illnesses linked to serotyped pathogens in Australia, Europe and the United States [ 30 , 31 ]. Our results suggest this level of prevention is attainable even in the early stages of WGS source tracking implementation.…”
Section: Discussionmentioning
confidence: 99%
“…Routine sequencing of the isolates received by the NRC would result in a representative database of circulating strains that enables the estimation of background diversity in the population and a better discrimination of new outbreak isolates [ 6 ]. From an economic perspective, Alleweldt et al [ 21 ] showed that only 0.2–1.1% of reported salmonellosis cases would need to be avoided each year through the use of WGS (e.g. by earlier outbreak detection) in order to make its implementation cost-neutral from a public health perspective.…”
Section: Discussionmentioning
confidence: 99%
“…by earlier outbreak detection) in order to make its implementation cost-neutral from a public health perspective. In addition, reference laboratories that deal with a high volume of samples achieve a lower per-sample cost than smaller institutions processing a lower amount of samples and the implementation at a central level would alleviate infrastructure investments and staffing requirements [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…New diagnostic tools such as unbiased and targeted next-generation sequencing (NGS) are being explored as options to improve surveillance as these allow to determine causes of unexplained disease outbreaks, trace and link sources of disease transmission, and facilitate a better understanding of how viruses and bacteria pass from animal to humans. With NGS, the same platforms and sometimes even the same protocols can be used for the analysis of viruses, bacteria, genes and parasites with the potential for cost saving through economies of scale (economies of scale occur when the costs per unit decrease when produced quantities increase, as total costs can be divided among more units), improving its affordability also for lower income countries 3 4. As most emerging infectious diseases are zoonotic, further improvements could come from incorporating concepts from ‘One Health’, integrating capacities across human and animal health sectors.…”
Section: The Benefits Of Improving Disease Surveillancementioning
confidence: 99%